Performance Analysis of Frame Relay Network Using OSPF (Open Shortest Path First) and MPLS (Multi-Protocol Label Switching) based on GNS3 - Andi Harits; Moch. Fahru Rizal; Periyadi Periyadi (IJAIT (International Journal of Applied Information Technology), 2017)
Communication today requires a secure, reliable and efficient network, especially on enterprise networks. This research focuses on combining advantages from Frame Relay, MPLS and OSPF into a modeled multi-site network. The combination is compared to the original OSPF network and analyzed for its throughput, packet loss, and delay. To meet the demand for efficient and resilient network, and to emphasize the advantages of MPLS-OSP as well as to avoid traffic shifting, specific network topology models are applied: full mesh with virtual circuit in core network connected to OSPF nodes for the rest. From analysis and comparison of network quality values obtained at, this combination attests to be reliable and robust network architecture without trading off its efficiency. The average throughput value of the combination networks was 18.47 bps, which is better compared to the OSPF. The average delay and packet loss from combination network also show better results, which are 59.90ms and 2.01% respectively. The results shows that the combination of Frame Relay, OSPF andMPLS generates better performance as well as significant improvement in network security.